Externalized transapical guidewire technique for complex aortic disease: a single-centre experience. (22nd October 2018) - Murakami, Takashi; Morisaki, Akimasa; Nishimura, Shinsuke; Takahashi, Yosuke; Sakon, Yoshito; Nakano, Mariko; Sohgawa, Etsuji; Fujii, Hiromichi; Shibata, Toshihiko
Abstract: OBJECTIVES: The through-and-through guidewire technique has been utilized for safe advancement of a high-profile stent graft delivery system through the tortuous aorta. A brachial-to-femoral configuration is most commonly established, but a few alternatives have been described. This study aimed to report our experience with the externalized transapical guidewire (ETAG) technique in patients who underwent thoracic endovascular aortic repair (TEVAR) and to explore its utility, feasibility and safety. METHODS: Patients who underwent TEVAR between April 2015 and March 2017 were retrospectively reviewed, and 5 patients who underwent the procedure with the ETAG technique were found eligible for the study. Indications for the ETAG technique were the following challenging aortic anatomical configurations: (i) severely angulated aorta in 3; (ii) proximity of the proximal landing zone to the aortic valve in 2; (iii) a limited proximal landing zone in 1; and (iv) complex atheroma predominantly on the greater curvature of the aorta in 3 patients. RESULTS: TEVAR was completed in all cases. The ETAG technique was utilized in all patients. The delivery system tip was navigated along the lesser curvature of the aortic arch as it was advanced. During deployment, conformability was increased by pushing both ends of the wire. Tip retrieval was also enhanced in 3 patients. Patients with complex aortic atheroma had no embolic complications. All patients survived TEVAR, but 1 patient with an aorto-oesophageal fistula did not survive the second-stage oesophagectomy. Postoperative complications included delayed cardiac tamponade requiring drainage in 2 patients. CONCLUSIONS: The ETAG technique was useful in overcoming several anatomical challenges encountered during TEVAR. Contact of the delivery system with the greater curvature of the aortic arch could be avoided with this technique, potentially reducing embolization risk related to the complex aortic arch atheroma.